Les politiques indignés sur les sites internet - Pachocińska, Elżbieta (Studia Romanica Posnaniensia, 2015)
Indignation in the political discourse has a long rhetoric tradition because of its moral aspect. This article focuses on the discursive construction of this emotion by French politicians in their communiqué posted on officials websites and on their twitter. It will be asked (1) how expression of indignation affects discursive structure, (2) how it can be inferred referring to our stereotypes, (3) how the emotional involvement contributes to positive ethos of politicians. Our analysis is based on the study of emotion in discourse proposed by Ch. Plantin (2011), the notion of subjectivity in language (C. Kerbrat-Orecchioni 1980) and the concept of ethos D. Maingueneau (1999).